Rapid thinning of the late Pleistocene Patagonian Ice Sheet followed migration of the Southern Westerlies. - Boex; Fogwill, CJ; Glasser, NF; Hein, A; Schnabel, C; Harrison, S (Scientific Reports, 2013)
Here we present the first reconstruction of vertical ice-sheet profile changes from any of the Southern Hemisphere's mid-latitude Pleistocene ice sheets. We use cosmogenic radio-nuclide (CRN) exposure analysis to record the decay of the former Patagonian Ice Sheet (PIS) from the Last Glacial Maximum (LGM) and into the late glacial. Our samples, from mountains along an east-west transect to the east of the present North Patagonian Icefield (NPI), serve as ¿dipsticks' that allow us to reconstruct past changes in ice-sheet thickness, and demonstrates that the former PIS remained extensive and close to its LGM extent in this region until ~19.0 ka. After this time rapid ice-sheet thinning, initiated at ~18.1 ka, saw ice at or near its present dimension by 15.5 ka. We argue this rapid thinning was triggered by a combination of the rapid southward migration of the precipitation bearing Southern Hemisphere (SH) westerlies and regional warming.